2011
DOI: 10.1002/ar.21535
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Analysis of Mandibular Morphogenesis by Micro‐CT‐Based Mouse and Alizarin Red S‐Stained‐Based Human Studies During Development

Abstract: Prenatal development of the mandible is an important factor in its postnatal function. To examine quantitatively normal and abnormal developmental changes of the mandible, we here evaluated morphological changes in mineralizing mandibles by thin-plate spline (TPS) including bending energy (BE) and Procrustes distance (PD), and by Procrustes analyses including warp analysis, regression analysis, and discriminant function analysis. BE and PD were calculated from lateral views of the mandibles of mice or of human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…To examine the deformation of 2D morphology in biological structures, the minimized total BE can be used as an index because the minimized BE represents the minimized curvature of the plate (35), therefore, the thin-plate spline can be useful to compare the morphological difference during organ development between two developmental stages or two individuals. A difference in mandible shape could be detected between Ror2-knockout and heterozygous or wildtype mice at E18.5 using BE, while BE revealed no difference between the Ror2 heterozygous and wildtype mice, which have similar morphology (36). The thin-plate spline is also used for registration between the medical images by selection of the landmarks, i.e.…”
Section: Quantification Of the Change In The Morphological Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine the deformation of 2D morphology in biological structures, the minimized total BE can be used as an index because the minimized BE represents the minimized curvature of the plate (35), therefore, the thin-plate spline can be useful to compare the morphological difference during organ development between two developmental stages or two individuals. A difference in mandible shape could be detected between Ror2-knockout and heterozygous or wildtype mice at E18.5 using BE, while BE revealed no difference between the Ror2 heterozygous and wildtype mice, which have similar morphology (36). The thin-plate spline is also used for registration between the medical images by selection of the landmarks, i.e.…”
Section: Quantification Of the Change In The Morphological Structuresmentioning
confidence: 99%
“…Similarly, the Procrustes distance is the sum of the squared distances between corresponding landmarks on the images, and can be used to examine the shape difference by comparing the configurations of the landmarks between two structures (35,36).…”
Section: Quantification Of the Change In The Morphological Structuresmentioning
confidence: 99%
“…Various anatomical components of the mouse embryo head have been examined after staining with OT and embedding in paraffin; these being the trigeminal ganglion (Aoyagi et al, ) and Meckel's cartilage (Aoyagi et al, ). A highly detailed mathematical analysis of mandibular shape in fixed GD 14.5–18.5 embryos from wild‐type and knockout mice of receptor tyrosine kinase‐like orphan receptor 2 showed that these mandibles could be separately identified (Rafiq et al, ). In another knockout mouse for a protein kinase A regulatory subunit ( Prkar1a ), micro‐CT showed qualitative and quantitative changes in the neural crest‐derived bones of the face on GD 17.5 (Jones et al, ).…”
Section: Embryo Imagingmentioning
confidence: 99%